2017
DOI: 10.1044/2016_jslhr-h-16-0066
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Processing of Older Adults With Probable Mild Cognitive Impairment

Abstract: Older adults with cognitive impairment not only have difficulty with competing acoustic signals but may also show poor temporal processing. The profile of auditory processing deficits among older adults with cognitive impairment may include multiple domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 49 publications
1
26
1
Order By: Relevance
“…Hearing loss is generally considered as an increase in average pure tone thresholds. But hearing ability is beyond pure tone sensitivity and includes more factors such as frequency selectivity, temporal coding fidelity, temporal encoding, intensity resolution, loudness, etc., which are not normally measured during an audiometric evaluation [6]. As we expected, the results of this study showed that speech perception in quiet did not differ significantly between the two groups.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Hearing loss is generally considered as an increase in average pure tone thresholds. But hearing ability is beyond pure tone sensitivity and includes more factors such as frequency selectivity, temporal coding fidelity, temporal encoding, intensity resolution, loudness, etc., which are not normally measured during an audiometric evaluation [6]. As we expected, the results of this study showed that speech perception in quiet did not differ significantly between the two groups.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have provided evidence of impairment in central auditory processing in individuals with MCI. It has been shown that their hearing performance is lower than expected, especially in the presence of background noise or competitive noise [6]. According to previous studies, it seems that central auditory processing disorders (CAPDs) are more common in older people who are more likely to develop cognitive problems, including MCI and Alzheimer’s disease [7].…”
Section: Introductionmentioning
confidence: 99%
“…As well, presumably because of neurodegenerative deficits in inter-hemispheric communication or integrity [ 37 ], they may display a disproportionate “right ear advantage”, i.e., decreased comprehension of information presented to the left ear [ 27, 38 ]. MCI patients typically show similar but lesser difficulties [ 39 ] that are, nonetheless, distinct from those associated with subjective memory complaints only [ 25 ]. Importantly, impairment in these abilities in symptomatic persons is related to areas of the brain that are particularly vulnerable to AD neurodegeneration [ 29–31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SSI-ICM test appears to be sensitive to the decline of CAP skills in MCI populations and accurately predicts the future clinical diagnosis of AD (Gates et al, 2008 andEdwards et al, 2017). Gates et al (2008) found that individuals with a diagnosis of MCI performed significantly poorer on the 0 dB SNR condition of the SSI-ICM compared to a control group.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have previously investigated the CAP skills in individuals diagnosed with MCI (Idrizbegovic et al, 2013;Edwards et al, 2017) and dementia (Gates et al, 2011;Golden et al, 2015;Quaranta et al, 2015). However, to date, no study has investigated the CAP skills in individuals with subjective memory complaints (SMCs).…”
Section: Introductionmentioning
confidence: 99%